2020
DOI: 10.1186/s12870-020-02478-1
|View full text |Cite
|
Sign up to set email alerts
|

SH1-dependent maize seed development and starch synthesis via modulating carbohydrate flow and osmotic potential balance

Abstract: Background As the main form of photoassimilates transported from vegetative tissues to the reproductive organs, sucrose and its degradation products are crucial for cell fate determination and development of maize kernels. Despite the relevance of sucrose synthase SH1 (shrunken 1)-mediated release of hexoses for kernel development, the underlying physiological and molecular mechanisms are not yet well understood in maize (Zea mays). Results Here, we identified a new allelic mutant of SH1 generated by EMS muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…In this respect, ethyl methanesulfonate (EMS) is one of the most effective, reliable, and powerful mutagens; treating plants with EMS could destroy their nuclear DNA and randomly induce new mutations in the process of DNA repair (Greene et al, 2003;Jain, 2010). Creating new germplasm through EMS has been implemented for many crops, such as barley (Caldwell et al, 2004), rapeseed (Lee et al, 2018), potato (Moon et al, 2018), rice (Serrat et al, 2014), wheat (Wang et al, 2018), maize (Zhang et al, 2020a), and Chinese cabbage (Lu et al, 2016). Notably, Jankowicz-Cieslak et al (2012) treated the meristem of banana stem tips with EMS and obtained high-density GC-AT base pair transition mutations, which demonstrated the high efficiency of EMS in banana germplasm innovation.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, ethyl methanesulfonate (EMS) is one of the most effective, reliable, and powerful mutagens; treating plants with EMS could destroy their nuclear DNA and randomly induce new mutations in the process of DNA repair (Greene et al, 2003;Jain, 2010). Creating new germplasm through EMS has been implemented for many crops, such as barley (Caldwell et al, 2004), rapeseed (Lee et al, 2018), potato (Moon et al, 2018), rice (Serrat et al, 2014), wheat (Wang et al, 2018), maize (Zhang et al, 2020a), and Chinese cabbage (Lu et al, 2016). Notably, Jankowicz-Cieslak et al (2012) treated the meristem of banana stem tips with EMS and obtained high-density GC-AT base pair transition mutations, which demonstrated the high efficiency of EMS in banana germplasm innovation.…”
Section: Introductionmentioning
confidence: 99%
“…In our RNA-seq results, almost all of the DEGs involved in this sucrose metabolism process exhibited a decreased expression level in smk7a , including the well-known genes SH1 , SH2 , and BT2 . SH1 encodes sucrose synthase, and the loss of the function of SH1 caused a significant reduction in the carbohydrates that flow to starch synthesis, ultimately contributing to the defects in the starch granule development and reduction of the starch content [ 46 ]. SH2 and BT2 encode AGPase and are rate-limiting enzymes in starch biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we hypothesize that the reduction of Zm00001d013173 may disrupt the sugar–lectin equilibrium, leading to more sugar release from the sugar–lectin complex, which in turn, results in the disruption of sugar homeostasis or osmotic balance, subsequently cell death and the formation EC. Indeed, an increase in sugar content and osmotic potential in the maize endosperm results in the formation of EC, as a result of the silencing of SH1 ( Zhang et al, 2020 ). On another hand, a previous study suggested that a strawberry homolog of Zm00001d013173, CBMFaEXP2, played a role in modifying and loosening plant cell wall structure ( Nardi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%